Variáveis de impacto na queda da mortalidade infantil no Estado de São Paulo, Brasil, no período de 1998 a 2008 - Lourenco, Eloisio do Carmo; Guerra, Luciane Miranda; Tuon, Rogerio Antonio; Silva, Sandra Maria Cunha Vidal e; Ambrosano, Glaucia Maria Bovi; Corrente, José Eduardo [UNESP]; Cortellazzi, Karine Laura; Vazquez, Fabiana de Lima; Meneghim, Marcelo de Castro; Pereira, Antonio Carlos (Abrasco, 2014)
This is an ecological, analytical and retrospective study comprising the 645 municipalities in the State of Sao Paulo, the scope of which was to determine the relationship between socioeconomic, demographic variables and the model of care in relation to infant mortality rates in the period from 1998 to 2008. The ratio of average annual change for each indicator per stratum coverage was calculated. Infant mortality was analyzed according to the model for repeated measures over time, adjusted for the following correction variables: the city's population, proportion of Family Health Programs (PSFs) deployed, proportion of Growth Acceleration Programs (PACs) deployed, per capita GDP and SPSRI (Sao Paulo social responsibility index). The analysis was performed by generalized linear models, considering the gamma distribution. Multiple comparisons were performed with the likelihood ratio with chi-square approximate distribution, considering a significance level of 5%. There was a decrease in infant mortality over the years (p < 0.05), with no significant difference from 2004 to 2008 (p > 0.05). The proportion of PSFs deployed (p < 0.0001) and per capita GDP (p < 0.0001) were significant in the model. The decline of infant mortality in this period was influenced by the growth of per capita GDP and PSFs.

Trata-se de estudo ecológico analítico, retrospectivo, composto pelos 645 municípios do Estado de São Paulo, cujo objetivo foi verificar a relação entre variáveis socioeconômicas, demográ- ficas e modelo de atenção, em relação ao coeficiente de mortalidade infantil, no período de 1998 a 2008. Foi calculada a proporção de variação mé- dia anual para cada indicador por estrato de cobertura. A mortalidade infantil foi analisada segundo modelo de medidas repetidas no tempo, ajustado para as variáveis de correção: população do município, proporção de PSF implantado, propor- ção de PACS implantado, PIB per capita e IPRS (índice paulista de responsabilidade social). A aná- lise foi realizada por modelos lineares generalizados, considerando a distribuição gama. Compara- ções múltiplas foram realizadas pela razão de verossimilhança com distribuição aproximada quiquadrado, considerando-se nível de significância de 5%. Houve diminuição da mortalidade infantil no decorrer dos anos (p < 0,05), não havendo diferença significativa de 2004 a 2008 (p > 0,05). A proporção de PSF implantado (p < 0,0001) e o PIB per capita (p < 0,0001) foram significativos no modelo. A queda da mortalidade infantil no período analisado foi influenciada pelo crescimento do PIB per capita e pelo modelo Saúde da Família.
Impact variables on the decline in infant mortality in the state of Sao Paulo, Brazil: 1998-2008
Keywords: Infant mortality; Socioeconomic factors; National strategies; Mortalidade infantil; Fatores socioeconômicos; Estratégias nacionais